Handbook of normative data for neuropsychological assessment - Mitrushina, Maura N., ....- (New York : Oxford University Press, 2005)
When Handbook of Normative Data for Neuropsychological Assessment was published in 1999, it was the first book to provide neuropsychologists with summaries and critiques of normative data for neuropsychological tests. The Second Edition, which has been revised and updated throughout, presents data for 26 commonly used neuropsychological tests, including: Trailmaking, Color Trails, Stroop Color Word Interference, Auditory Consonant Trigrams, Paced Auditory Serial Addition, Ruff 2 and 7, Digital Vigilance, Boston Naming, Verbal Fluency, Rey-Osterrieth Complex Figure, Hooper Visual Fluency, Design Fluency, Tactual Performance, Wechsler Memory Scale-Revised, Rey Auditory-Verbal learning, Hopkins Verbal learning, WHO/UCLA Auditory Verbal Learning, Benton Visual Retention, Finger Tapping, Grip Strength (Dynamometer), Grooved Pegboard, Category, and Wisconsin Card Sorting tests. In addition, California Verbal learning (CVLT and CVLT-II), CERAD ListLearning, and selective Reminding Tests, as well as the newest version of the Wechsler Memory Scale (WMS-III and WMS-IIIA), are reviewed. Locator tables throughout the book guide the reader to the sets of normative data that are best suited to each individual case, depending on the demographic characteristics of the patient, and highlight the advantages associated with using data for comparative purposes. Those using the book have the option of reading the authors' critical review of the normative data for a particular test, or simply turning to the appropriate data locator table for a quick reference to the relevant data tables in the Appendices. The Second Edition includes reviews of 15 new tests. The way the data are presented has been changed to make the book easier to use. Meta-analytic tables of predicted values for different ages (and education, where relevant) are included for nine tests that have a sufficient number of homogeneous datasets. No other reference offers such an effective framework for the critical ev
Includes bibliographical references and index.
Testotheek
Keywords: Neuropsychological Tests; Neuropsychological tests -- Handbooks, manuals, etc; Neuropsychologie -- Diagnostiek; Psychologische tests; Reference Values; Reference values (Medicine) -- Handbooks, manuals, etc